Alumni series : Pharmacoeconomics and its important in pharmacy / Hasryn Azzuar Mohd Khairy - Mohd Khairy, Hasryn Azzuar (Faculty of Pharmacy, 2023)
Pharmacoeconomics refers to the scientific discipline that compares the value of one pharmaceutical drug or drug therapy to another and it is a sub-discipline of health economics. Pharmacoeconomic research assesses the financial value, efficacy, or effects on quality of life of a pharmaceutical medication as well as its costs (represented in monetary terms). Pharmacoeconomic studies help to determine the most efficient and scientifically sound way to allocate healthcare resources. Pharmaceutical economic evaluation is the focus of pharmacoeconomic, which may employ cost-minimization, cost-benefit, cost-effectiveness, or cost-utility analysis. The primary outcome of interest in pharmacoeconomic analyses is quality-adjusted life years (QALY), and much research uses cost-per-QALY analysis. Randomised controlled trials and decision-analytic modelling techniques are used in economic evaluations.